Estrategias didácticas para la comprensión y expresión oral en primer grado de educación general básica en la unidad educativa intercultural bilingüe Mariscal Sucre del cantón Cayambe - Guaján Chancosi, Katherine Rocío (2018)
This work entitled "Teaching Strategies and speaking in the first year of Basic General Education Unit Intercultural Bilingual "Mariscal Sucre", aims to provide a methodological contribution consisting of four teaching strategies from non-participant observation to teaching work. To get to design the methodology has sought to understand the following theoretical aspects: cognitive development, in the area of language, children 6 years current curriculum, teaching strategies and the theory of cognitive development Piaget. This work began with the identification of the problems at the institutional level consisting of the need to improve the teaching methodology in terms of the use of teaching strategies for language and literature. The methods used for this proposal were: the qualitative one with its non-participant observation technique for the identification of the problem; the analytical one that helped in the determination of the topics and subtopics included in the theoretical and deductive framework that guided the construction of didactic strategies. The design of four strategies as a result of the above process contains: a dramatization, a popular game, couplets and an excursion, designed from the cognitive development of children level linguistic conceptualization, review the curriculum and cognitive theory of Piaget. The work has the following structure: problem, objectives, theoretical foundation that contains, among other topics, the conceptualization of oral expression and comprehension, linguistic consciences, the high school curriculum; methodology, methodological proposal, conclusions and recommendations, bibliography and annexes.